Pharmaceutico-Analytical study of Brihatsindooradya Taila and its Malahar - Sumitra; Kumar, Sanjay; Rajoria, Kshipra; Verma, Vijay Shankar (International Research Journal of Ayurveda & Yoga, 2022)
The skin is the first organ of the body to come into contact with environmental factors like physical, chemical, and biological pollutants. The skin serves as a mirror, reflecting both internal and external pathology and thus assisting in the diagnosis of illness. Skin problems can affect persons of all ages, from infants to the elderly, and can cause deformity, disability, and other issues. This present study entitled “Pharmaceutico-Analytical study of Brihatsindooradya Taila and its Malahar ”. was carried out with a view to standardize Brihatsindooradya Taila and prepare its modified forms viz. ointment. The present study is framed under 7 main sections viz. Introduction, Drug Review, Pharmaceutical Study, Analytical Study, Discussion, Summary and Conclusion. Aim: The aim is to prepare BST as per textual guidelines and its malahar which is a modified dosage form & to analyze the prepared sample of BST and its malahar as per standard parameter. Materials and Methods: Pharmaceutical study was conducted with the Vatsnabha shodhan, Tandulodaka nirmana, Sindoora shodhan, Sarshapa Taila murchchhana, preparation of Brihatsindooradya Taila (BST) and preparation of Brihatsindooradya Malhar (BSM). Results: The findings for analytical parameters were found to be satisfactory for quality assurance. Assay of heavy metals (Pb, Cd, As, Hg),Total bacterial count and Total fungal count are under the permissible limit depicted in the study. Specific pathogens and aflatoxins (B1, B2, G1, G2) are absent in all samples. The malahar also had good thermal stability, easily washable, non-irritant and free from pathogens and no rancidity. In HPTLC finger printing van though a few RF values were similar for both BST and BSM the chemical constituent could not be identified due to the absence of standard marker.